PENINGKATAN AKTIVITAS BELAJAR SISWA PADA PEMBELAJARAN IPA DENGAN MODEL TEMUAN TERBIMBING DI SEKOLAH DASAR - Sinurat, Maruli Tua; Uliyanti, Endang; Sugiyono, Sugiyono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstrakThe purpose of this research is to describe the improvement of students’ learning activity in science learning using Temuan Terbimbing Model. The method of this research is descriptive in form of classroom action research with collaborative participation as the charachteristics. Subject of this research is fifth grade students of SD Negeri 18 Pelangor. Technique of collecting data is direct observation .Tools of data collection is observation sheets. The collected data is analyzed in percentage and mean. This research is done in two cycle. Based on the data analysis, teacher’s ability on planning in cycle I is 3.34 and 3.68 in cycle 2, the improvement is 0.34. Meanwhile, teachers’ability on implementing in cycle I is 3.39 and in the second cycle 3.74, the improvement is 0.35. Students’ learning activity in the first cycle is 41.67% and 72.29%, the improvement is 31.47%.In conclusion, Temuan Terbimbing Model can improve students learning activity in , Ilmu Pengetahuan Alam learning Keywords :Learning Activity, TemuanTerbimbing Model, Ilmu Pengetahuan Alam